Priority assessment of transportation projects in the central Witwatersrand area of South Africa. - Conway, Peter Joseph. (My University, 1994)
Existing priority assessment procedures are reviewed with a view to identifying a methodology which will be appropriate for use in the Central Witwatersrand Regional services Council area. It is concluded that a two stage methodology is most appropriate, adopting a.successive sub-setting technique and a detailed sufficiency rating technique respectively, The methodology is tested on the 1992/93 project list.
A thesis submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science
Keywords: Transportation -- South Africa -- Gauteng -- Planning.; Transportation -- South Africa -- Gauteng.